GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 1795 species occurrences available in GBIF matching the query: TaxonKey: Amaranthus blitum L. or Abelmoschus caillei (A. Chev.) J.M.C. Stevels or Allium cepa L. or Artocarpus altilis (Parkinson ex F.A.Zorn) Fosberg or Annona reticulata L. or Adansonia digitata L. or Amaranthus tricolor L. or Allanblackia floribunda Oliv. or Anacardium occidentale L. or Balanites aegyptiaca (L.) Delile or Annona senegalensis Pers. or Amaranthus cruentus Willd. ex Roxb. or Basella alba L. or Adansonia kilima Pettigrew, K.L.Bell, Bhagw., Grinan, Jillani, Jean Mey., Wabuyele & C.E.Vickers Geometry: POLYGON((-26.850585 17.266727,-21.401367 20.220965,-17.446289 24.206889,-14.985351 26.313112,-13.359375 27.916766,-10.634765 29.458731,-10.458984 32.212801,-7.910156 35.101934,-6.525878 35.889050,-5.009765 36.102376,-2.570800 35.764343,-0.922851 36.191092,1.801757 36.967449,3.493652 37.405073,6.613769 37.561996,9.206542 37.735969,11.623535 37.666429,11.843261 36.862042,11.887207 35.817813,11.997070 34.705493,12.502441 33.961586,13.754882 33.413102,16.523437 32.787274,19.599609 32.676372,20.061035 33.284619,23.664550 33.906895,25.773925 32.528289,28.300781 31.989441,29.355468 32.249974,31.992187 31.989441,33.706054 32.008075,34.145507 31.494261,34.343261 30.977609,34.552001 30.297017,34.859619 29.343875,34.595947 28.420391,34.497070 28.139815,34.442138 27.625140,34.793701 26.293415,35.760498 24.686952,36.309814 23.976214,37.133789 22.238259,38.034667 20.210656,38.770751 18.354525,39.605712 17.109292,41.462402 15.707662,43.813476 12.082295,48.054199 11.652236,50.207519 12.060809,51.394042 12.211180,52.250976 9.990490,52.009277 7.732765,52.294921 -2.986927,57.832031 -15.368949,59.611816 -20.488773,53.261718 -26.588527,42.802734 -32.916485,26.894531 -35.029996,17.490234 -36.456636,15.908203 -33.797408,11.074218 -22.917922,4.042968 -11.695272,-12.304687 4.214943,-27.246093 13.068776,-26.850585 17.266727)) HasCoordinate: true HasGeospatialIssue: false BasisOfRecord: Specimen. The dataset includes 1795 records from 39 constituent datasets: 5 records from Phanerogamic Botanical Collections (S). 20 records from PRECIS (KwaZulu-Natal Herbarium). 2 records from University of Vienna, Institute for Botany - Herbarium WU. 676 records from Naturalis Biodiversity Center (NL) - Botany. 148 records from PRECIS. 45 records from IICT Herbário LISC. 1 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 14 records from Herbier du Bénin. 18 records from Endemic plants of the Congo basin. 10 records from Herbarium of the Université Libre de Bruxelles. 25 records from Australia's Virtual Herbarium. 4 records from Herbier National de Mauritanie (HNM). 1 records from NMNH occurrence DwC-A. 3 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 4 records from INERA-Luki reservation herbarium (CABIN project). 224 records from Tropicos Specimen Data. 10 records from Natural History Museum (London) Collection Specimens. 2 records from Natural History Museum, Vienna - Herbarium W. 2 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 24 records from The AAU Herbarium Database. 20 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 3 records from DAV UC Davis Center for Plant Diversity. 60 records from EURISCO, The European Genetic Resources Search Catalogue. 3 records from CRSN-Lwiro Herbarium, Kahuzi-Biega National Park (CABIN project). 22 records from Herbier Ecole de Faune. 10 records from Herbarium Senckenbergianum (FR). 232 records from University of Ghana - Ghana Herbarium. 27 records from Herbarium togoense. 54 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Herbier_CNSF. 1 records from Bernice P. Bishop Museum. 3 records from Royal Botanic Garden Edinburgh Herbarium (E). 3 records from tan-database. 68 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 1 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 1 records from Université Pédagogique Nationale de Kinshasa (UPN) - Données botaniques (2011)- Projet CABIN. 39 records from Herbier CNRST/INERA. 3 records from tan-database. 6 records from Geneva Herbarium – General Collection (G). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences